Optimizing Rumpon-Based Green Human Resource Management to Improve Fishermen’s Quality of Life: The Role of Digital Literacy toward Sustainable Development - K, Ahmad; Akbar Azis (MANDAR: Management Development and Applied Research Journal, 2025)
This research aims to examine the influence of rumpon-based Green Human Resource Management (GHRM) practices on fishermen’s quality of life in Majene Regency, emphasizing the mediating and moderating role of digital literacy within the framework of sustainable development. A quantitative approach was applied using a survey of 395 fishermen, analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method.The findings reveal that: (1) Rumpon-based GHRM significantly and positively affects fishermen’s quality of life and marine ecosystem sustainability; (2) Digital literacy has a positive impact on fishermen’s well-being; (3) Digital literacy mediates the relationship between GHRM and quality of life; and (4) Digital literacy strengthens the link between GHRM practices and marine ecosystem sustainability. These results highlight that integrating environmentally conscious HRM practices with digital literacy grounded in local wisdom provides an effective pathway for improving fishermen’s welfare while ensuring the conservation of coastal ecosystems